A gestão que não aparece : estudo etnográfico de um projeto de pesquisa em rede da Embrapa - Guimarães, Maria Katy Anne Valentim de Oliveira, 1969- (2013)
Orientadores: Marko Synésio Alves Monteiro, Milena Pavan Serafim